Effect of pulsed substrate biasing on macroparticle in vacuum arc - Romashchenko, E.V.; Bizyukov, A.A.; Girka, I.О. (Вопросы атомной науки и техники, 2019)
An analytical model of the interaction of macroparticle (MP) with vacuum arc plasma in plasma immersion ion implantation (PIII) is presented. The proposed model is based on combination of the theory of charge dynamics of MP and sheath model for PIII. In the framework of this model, the MP charge dynamics during voltage pulse as well as during interval between pulses is investigated. It is obtained that MP charge and MP behavior depend on pulsed bias parameters such as pulse duration, duty cycle and bias amplitude. It is shown that pulsed substrate biasing is effective method to control of the MPs in plasma processing. Подано аналітичну теорії взаємодії макрочастинки (МЧ) з плазмою вакуумної дуги при плазмовій імерсійній іонній імплантації (ПІІІ). Запропонована модель базується на комбінації теорії динаміки зарядження МЧ та теорії шару для ПІІІ. У рамках цієї моделі досліджується динаміка зарядження як протягом імпульсу, так і в інтервал між імпульсами. Отримано, що заряд та поведінка МЧ залежать від параметрів імпульсного потенціалу, таких як тривалість імпульсу, період та амплітуда потенціалу. Показано, що застосування імпульсного потенціалу є ефективним методом контролю за МЧ у плазмових процесах. Представлена модель взаимодействия макрочастицы (МЧ) с плазмой вакуумной дуги при плазменной иммерсионной ионной имплантации (ПИИИ). Предложенная модель основана на комбинации теории динамики заряда МЧ и модели слоя для ПИИИ. В рамках этой модели исследуется динамика заряда МЧ как во время импульса, так и в интервале между импульсами. Получено, что заряд и поведение МЧ зависят от параметров импульсного потенциала, таких как длительность импульса, период и амплитуда потенциала. Показано, что применение импульсного потенциала является эффективным методом контроля МЧ в плазменных процессах.